Value-free instructional practices as a correlate of anti-corruption politics in Nigeria - Ahmad Rufai, Saheed (Penerbit Universiti Kebangsaan Malaysia, 2014)
The thesis of the sociological foundations of the curriculum is that the outlook, orientation or social condition of any society is a reflection of its education system. Accordingly, the school is regarded as an agent of change for society which is why values and vices are normally traced to curricular provisions and instructional practices, in the educational parlance. The central argument of this paper is that the perceived inefficacy of the various anti-corruption policies introduced by successive administrations in Nigeria, is in part, traceable, to the growing value-free nature of instructional practices at various levels of education in the country. The paper, which is analytical in method and situated within the broad scholarship of pedagogical ethics, highlights some of the pitfalls of anti-corruption politics in the country and attempts to correlate such pitfalls with its largely value-free educational system. The significance of such study lies in its potential to contribute scholarly to the ongoing debates and growing concern over corruption in Nigeria, improve our understanding of the subject and, more importantly, offer a curricularist’s perspective on the subject, which itself is capable of contributing towards a change in the landscape of education, for character formation and nation building in the country.